2021
DOI: 10.3389/fmars.2021.719608
|View full text |Cite
|
Sign up to set email alerts
|

Mesopelagic Fish Protein Hydrolysates and Extracts: A Source of Novel Anti-Hypertensive and Anti-Diabetic Peptides

Abstract: The abundance of fish and zooplankton (1 × 109 tons to 7 × 1010 tons) in the mesopelagic zone of the ocean is a source of novel raw materials that provides opportunities for sustainable new product development. The peculiar conditions of light and pressure in this ecological zone and the position of the specific organisms in the marine food chain results in diversity in their bio-composition. Mesopelagic fish are an underutilized resource, rich in proteins and omega-3 oils, and present opportunities to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In vitro and in vivo studies with dogs showed that these conditionally essential fatty acids ( 19 ) play important metabolic roles in cell membrane fluidity, neural development, cognitive status, visual acuity, and inflammatory and immunologic responses ( 61–63 ). Similarly, the CP content and amino acid profile of seafood and crustacean hydrolysates might differ depending on the primary source of protein (species and part of the animal), enzyme source, and hydrolysis conditions ( 17 , 64 ). An earlier study ( 37 ) showed that in shrimp hydrolysate obtained from the enzymatic hydrolysis of heads and cephalothoraxes of Litopenaeus vannamei , as the one used in the current study, lysine and leucine were the essential amino acids found in the highest amounts, and glutamic acid plus glutamine were the main non-essential amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies with dogs showed that these conditionally essential fatty acids ( 19 ) play important metabolic roles in cell membrane fluidity, neural development, cognitive status, visual acuity, and inflammatory and immunologic responses ( 61–63 ). Similarly, the CP content and amino acid profile of seafood and crustacean hydrolysates might differ depending on the primary source of protein (species and part of the animal), enzyme source, and hydrolysis conditions ( 17 , 64 ). An earlier study ( 37 ) showed that in shrimp hydrolysate obtained from the enzymatic hydrolysis of heads and cephalothoraxes of Litopenaeus vannamei , as the one used in the current study, lysine and leucine were the essential amino acids found in the highest amounts, and glutamic acid plus glutamine were the main non-essential amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is significant potential for utilizing the remaining by-products that are not intended for dietary oil production. These can be repurposed to produce bioactive peptides for human consumption [14], or feed for the expanding aquaculture sector [3]. Increasing the oil recovery from 27% to 90% could yield an additional 70% of EPA + DHA, highlighting the importance of developing optimal processing technologies.…”
Section: Dietary Lipids From the Mesopelagic Biomassmentioning
confidence: 99%
“…Several studies have evaluated the biochemical composition of different mesopelagic species [2,3,[13][14][15][16], but scientific literature is scarce on the production of marine-derived ingredients, particularly marine oils. The potential of these species has also been evaluated based on predicted biomass estimations, but it is documented that mesopelagic catch rates are highly variable [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mesopelagic species include Maurolicus muelleri (Mueller's Pearlside) and Meganyctiphanes norvegica (Northern Krill) [1]. Recent work in the MEESO and SUMMER EU H2020 projects identified Angiotensin-1-converting enzymes (ACE-1) inhibitory, Dipeptidyl peptidase IV (DPP-IV) inhibitory and antimicrobial activities in hydrolysates and extracts generated from mixed mesopelagic fish trawls [2]. Additional studies by Aliyu and colleagues (2022) identified the antioxidant potential of hydrolysates generated from M. muelleri and Krill [3].…”
Section: Introductionmentioning
confidence: 99%